Peran mediasi kinerja keberlanjutan pada keberagaman gender dewan direksi terhadap agresivitas pajak - Safitri Rahmadani; Indriyana Puspitosari (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
This study aims to determine the effect of the board of director gender diversity on corporate tax aggressiveness and the mediation effect of sustainability performance. 84 samples selected of property & real estate sector companies listed on the Indonesia Stock Exchange from the period 2016-2021. Multiple regression was used to analyze the direct relationship between board director gender diversity and tax aggressiveness. A path analysis approach was employed to analyze the indirect relationship between board director gender diversity and tax aggressiveness through sustainability performance as a mediating variable. The results show that board director gender diversity has a positive effect on tax aggressiveness, board director gender diversity has no effect on sustainability performance, and sustainability performance has no effect on tax aggressiveness. Path analysis results did not find support for mediating the role of sustainability performance on the relationship between board director gender diversity and tax aggressiveness